Determinants of Romanians' Migration within the European Union: Static and Dynamic Panel Gravity Approaches - Adriana Ana Maria Davidescu; Vasile Alecsandru Strat; Raluca Mariana Grosu; Ion-Daniel Zgură (Amfiteatru Economic Journal, 2017)
The 1st of January 2007 marked Romania's accession to the European Union (EU) and represented its 'ticket' to a free access to the common market. This soon evolved into an important trigger for the increased migration flows from Romania towards the more developed western countries, members of the EU. Not only the opportunity of a free movement of persons – emerged with the integration - but also the existing socio-economic disparities between Romania and the more developed western countries in the EU, led to unidirectional migration flows. Using both static and dynamic panel gravity models, we aim to identify the main determinants of Romanians' migration towards 10 EU member states – Czech Republic, Denmark, Italy, Netherlands, Finland, Germany, Norway, Poland, Spain, and Sweden – for the period 2007-2014. Our empirical findings support the results of other studies performed on different economies. The most important pull factor for Romanians' migration is represented by the economic conditions in the destination countries, proxied by the GDP/capita. Other important pull factors fuelling Romanians' migration refer to the unemployment rate, life expectancy, education spending, and population density. A key role is also played by the existing social networks in the destination countries which are proxied in our model by the lagged migration flows.
Keywords: C23; F22; O15; O52; 330; international migration; Romania; panel data; static gravity model; dynamic gravity model